Analysis showing Total Number of Basque Children in England With Full Particulars of Their Parent's Circumstances
038-0074-001 ANALYSIS SHOWING TOTAL NUMBER OF BASQUE CHILDREN IN ENGLAND WITH FULL PARTICULARS OF THEIR PARENTS CIRCUMSTANCES. 1. Total number of children in England 1054 2. Categories which in the view of the Basque Children's Committee, and subject to individual investigations in all cases, can be repatriated 1. Both parents in Spain 145 2. Father dead, Mother in Spain 69 3. Father in Spain, Mother dead 21 4. Father abroad, Mother in Spain 47 5. Father in Spain, Mother abroad 50 6. Father's whereabouts unknown, Mother in Spain 43 7. Father in Spain, Mother's whereabouts unknown 13 8. Father dead, mother's whereabouts unknown 16 9. Father's whereabouts unknown, Mother dead 17 10. Both parents dead 56 477 3. Categories which in the opinion of the Basque Children's Committee should remain in England because it is impossible to restore them to their parents under existing war conditions 1. Both parents abroad 164 2. Both parents unknown 76 3. Both parents prisoners 24 4. Father in prison, mother in Spain 135 5. Father in Spain, mother in prison 1 6. Father prisoner, mother abroad 35 7. Father abroad, mother prisoner 2 8. Father prisoner, mother dead 8 9. Father dead, mother prisoner 1 10. Father in prison, mother unknown 14 11. Father dead, mother abroad 50 12. Father unknown, mother prisoner 14 13. Father abroad, mother dead 13 14. Father abroad, mother unknown 6 15. Father unknown, mother abroad 34 577 292/946/38/74(I)